The Northern Swedish Cohort (NoSCo) 1981 - Hammarström, Anne (Umeå University, 2017)
In 1981 a longitudinal study began that includes all pupils who attended or should have attended the last year of compulsory school in the municipality of Luleå. The population consists of 1083 pupils (506 girls and 577 boys) and this group has since been followed by repeated questionnaires, but also through personal meetings, interviews, blood pressure measurements and other Health examinations. The main purpose of the survey was to study the social and medical consequences such as unemployment leads among these young people, who find themselves in the joint between school, training and employment.

The questionnaire consisted of around 90 validated questions regarding social background, work situation, health, family situation, leisure time etc. The questionnaire was almost identical at all investigations. The cohort has been investigated with a comprehensive questionnaire — in 1981 (age 16 years), 1983 (age 18 years), 1986 (age 21 years), 1995 (age 30 years) and 2008 (age 43 years). Clinical measurements were performed in 1981, 1986 and 2008 and interviews were performed with key persons, such as the school nurses in 1981 and with the form teachers in 1981 and 1983. The subsample with early unemployed participants has been followed up with personal interviews since autumn 1981. Until now, they have been interviewed on average four times per person. The main topic has been the health consequences of unemployment.

One of survey results was that unemployment appears to have more serious health consequences for young people than for adults and that health consequences of youth unemployment persists to some extent in adulthood.

Purpose:

Initially, the overall objective of the research programme was to analyse the significance of unemployment in relation to mental health in adolescence for well-being and health status into adult age.

År 1981 påbörjades en longitudinell studie som omfattar alla elever som vårterminen det året skulle avsluta årskurs nio i grundskolan i Luleå kommun. Gruppen består av 1083 elever (503 flickor och 577 pojkar) och denna grupp har sedan dess följts med upprepade frågeformulär, men också genom personliga möten, intervjuer, blodtrycksmätningar och andra hälsoundersökningar. Huvudsyftet med undersökningen har varit att studera vilka sociala och medicinska konsekvenser som arbetslöshet medför bland de av ungdomarna som befinner sig i skarven mellan skola, utbildning och förvärvsarbete.

Frågeformuläret bestod av cirka 90 frågor om social bakgrund, arbetssituation, hälsa, familjesituation, fritid etc. Enkäten var nästan identisk i alla undersökningar. Kohorten har med följts upp fem gånger - 1981 (16 års ålder), 1983 (18 års ålder), 1986 (21 års ålder), 1995 (30 års ålder) och 2008 (43 års ålder). Kliniska undersökningar utfördes i 1981, 1986 och 2008 och intervjuer utfördes med nyckelpersoner såsom skolsköterskor 1981 och med klasslärare 1981 och 1983. De deltagare som tidigt blev arbetslösa har följts upp i ett delprov genom personliga intervjuer sedan hösten 1981. Hittills har de i genomsnitt intervjuats fyra gånger per person. Huvudtemat har varit hälsokonsekvenser av arbetslöshet.

Ett resultat av undersökningen var att arbetslöshet förefaller att få värre hälsokonsekvenser för unga än för vuxna och hälsokonsekvenserna av ungdomsarbetslöshet kvarstår i viss mån i vuxen ålder.

Syfte:

Syftet för forskningsprogrammet var initialt att analysera betydelsen av arbetslöshet i relation till psykisk hälsa i tonåren för välbefinnande och hälsotillstånd i vuxen ålder.
The Northern Swedish Cohort (NoSCo) 1981
Keywords: self-esteem; självkänsla; unemployment; arbetslöshet; ill health; ohälsa; marital status; civilstånd; mental health; psykisk hälsa; status in employment; tjänsteställning; youth employment; ungdomsanställning; return-to-work incentives; åtgärder för återgång till arbete; unemployed; arbetslösa; youth unemployment; ungdomsarbetslöshet; exercise (physical activity); motion (fysisk aktivitet); alcohol; alkohol; HEALTH; HÄLSA; General health and well-being; Allmän hälsa och välbefinnande; Unemployment; Arbetslöshet; Work Sciences; Arbetslivsstudier